2014
DOI: 10.1002/jez.1858
|View full text |Cite
|
Sign up to set email alerts
|

Precocial bird mothers shape sex differences in the behavior of their chicks

Abstract: Compared to mammals and altricial birds, evaluations of differences related to precocial birds' sex have often been limited to sexual behavior. Nevertheless, the extensive use of precocial bird models for investigating behavioral development issues requires in depth knowledge concerning the emergence of sex differences. Here, we evaluated behavioral differences between Japanese quail chicks in relation to their sex. We know that maternal influences are strong and early social environment shapes behavioral deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
(82 reference statements)
1
17
0
Order By: Relevance
“…The Open Field trial is a common way to measure exploratory behavior by quantifying the behavior of an animal in an unfamiliar open environment, where more movement and vocalization indicates more proactive behavior (Bertin & Richard‐Yris, ; Daisley et al., ; Formanek et al., ; Pittet et al., ). On 6 and 13 dph, each duckling was individually placed in an empty outdoor aviary room (5.5 × 2.5 m) with a grid system on the floor forming 0.25 × 0.25 m squares.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Open Field trial is a common way to measure exploratory behavior by quantifying the behavior of an animal in an unfamiliar open environment, where more movement and vocalization indicates more proactive behavior (Bertin & Richard‐Yris, ; Daisley et al., ; Formanek et al., ; Pittet et al., ). On 6 and 13 dph, each duckling was individually placed in an empty outdoor aviary room (5.5 × 2.5 m) with a grid system on the floor forming 0.25 × 0.25 m squares.…”
Section: Methodsmentioning
confidence: 99%
“…The Emergence trial is a common trial used to quantify boldness, where proactive individuals are more likely to emerge quickly from a sheltered area into an unknown environment than reactive individuals (Formanek et al., ; Pittet, Coignard, Houdelier, Richard‐Yris, & Lumineau, ; Pittet el al., ). On 8 and 15 dph, each duckling was placed in a wooden box (0.5 × 0.5 × 0.5 m) and given 1 min to acclimate (Pittet et al., , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first study in quail chicks did not report evidence of sex differences in social and emotional behaviors (Mills & Faure, ). But recently, Pittet, Houdelier, and Lumineau () showed fearfulness differences in motherless individuals, with males being more fearful than females. This sex difference was less strong in brooded chicks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, precedent study had shown that males are more sensitive (i.e. they called more) than females to the separation from their mothers at the end of the mothering period, an indication that the mother‐male chick relationship is stronger at that time (Aigueperse, Pittet, Nicolle, Houdelier, & Lumineau, ; Pittet, Houdelier, & Lumineau, ).…”
Section: Introductionmentioning
confidence: 99%